Corrigendum The Colombian integrated system of truth, justice, reparation and non-repetition (vol 15, pg 1011, 2017) (2018)
This is a correction notice for article mqx057 (DOI: https://doi-org.ez.urosario.edu.co/10.1093/jicj/mqx057), published on 25 December 2017. The authors regret that part of Hector Olasolo's affiliation was worded incorrectly. It read: 'Prof. Olasolo holds the Chair in International Law at the University of El Rosario (Colombia)'; however, it should have read as follows: 'Prof. Olasolo holds the Chair in International Law at Universidad del Rosario, Bogotá, Colombia.' This has now been corrected online. © 2018 Oxford University Press. All Rights Reserved.